Most Frequently Affected Body parts in Road Traffic Accidents Reporting to the Accident and Emergency Department of the Largest Tertiary Care hospital of Karachi in 2019 - zaeema Ahmer; Aisha Siddiqui (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction Injuries sustained during Road Traffic Accidents (RTAs) amounts to a serious public health crisis. The aim of the study was to determine the body parts most likely affected in an RTA in patients brought to Accident and Emergency (A&E) department of Jinnah Postgraduate Medical Centre (JPMC), the largest tertiary care hospital of Karachi. Method A descriptive cross-sectional study was done in January-March 2019 among 371 respondents aged 15-65 years. Study participants were recruited through non-probability convenience sampling. A structured questionnaire was used to collect data on sociodemographic variables and type, severity and nature of injury. Chi Square test was used to determine the significant difference between using safety precautions with body parts affected. All analysis was performed on SPSS version 20. Results Out of 371 study participants, 64.4% (n=239) were between 15-35 years with 91.9% (n=338) males. In 77.1% (n=286) cases, emergency medical services responded in less than one hour and first aid was provided by doctor to 95.7% (n=355) at hospital. In 82.5% (n=306) cases, private vehicles were involved, with 46.1% (n=171) motorcycles. In 79.8% (n=296) cases, bone injury was prevalent, with 57.1% (n=212) leg injuries, which was the most frequently affected body part. Majority, 56.2% of the study participants who did not wear seat belts had chest area affected (p=0.006).  Conclusion It is concluded that males of 15-35 years who were motorcyclists were more prone to RTAs with lower limbs more frequently being affected. Safety precautions like wearing seatbelts provide protection against RTAs.